José Martí, um intelectual na periferia capitalista: luta política na transição das estruturas de poder em Cuba (1890-1895) - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
Our dissertation intends to investigate a political-intellectual trajectory of José Martí (1853-1895), possibly the main ideologue of the struggle for the independence of Cuba (1895-1898). Our main source was his texts published in periodicals in the years 1890-1895. Of his diverse interests, two were in detail, in our study: his prominence in the field of journalism and party leader. The context of his performance took place during the transition period in the 1890s, which marked a rearrangement / update / modernization of power structures in Cuba, a transition from the colonial (spanish) model to (north american) imperialism. For the problematization of primary documentation (analytical / historiographical part), we start from a list of gramscian concepts (theoretical part), to assist us in this research itinerary. Our hypothesis is that Martí, from journalistic activity and party leadership, became an "organic intellectual" of the Cuban insurrectional movement (1895). This question, which has historically kept it coherent, has a radical political perspective.
Keywords: Martí; Movimento insurrecional cubano; Poder metropolitano espanhol; Contra-hegemonia; Insurrectionary cuban movement; Spanish metropolitan power; Counter-hegemony; CIENCIAS HUMANAS::HISTORIA; COMPORTAMENTO POLITICO::ATITUDE E IDEOLOGIAS POLITICAS; HISTORIA DA AMERICA::HISTORIA LATINO-AMERICANA